ʼA rhaṅʻ Sāsana mahātherʻ mratʻ saññʻ ... cī raṅʻ reʺ sāʺ toʻ mū ʼapʻ so Suttatthagaṇakkama dīpanī kyamʻʺ - Sāsana, ʼA rhaṅʻ, 1877-1927 (Sāsanahita Cā puṃ nhipʻ tuikʻ, 1928)
Treatise, gleaned from classical texts, on Pali grammar.